A new climatic chamber for studying soil–atmosphere interaction in physical models. Issue 6 (26th October 2018) - Lozada, Catalina; Caicedo, Bernardo; Thorel, Luc
Abstract : A new climatic chamber at the Universidad de Los Andes in Bogotá, Colombia has been designed and built to simulate atmosphere. It has been instrumented to measure various environmental variables, including relative humidity (RH), wind velocity, radiation and temperature. The climatic chamber has been calibrated so that it properly simulates each environmental variable as well as the heat-transfer mechanisms that affect desiccation in soil layers. First, a potential evaporation test was performed in a container filled with water. The weight of the water evaporated was measured, and the interaction with the artificial atmosphere was studied. Then, an actual evaporation test was performed on a soil layer, and the relations among environmental variables and soil properties such as soil temperature, water content and suction were determined. The principal results show the existence of a gradient of RH at the soil–atmosphere interface. Also, a comparison between potential and actual evaporation indicates that suction is the main soil property that affects the actual evaporation rate.